PENGEMBANGAN LEMBAR KERJA BERBASIS INKUIRI TERINTEGRASI KELOMPOK MATA PELAJARAN PEREKAT BANGSA UNTUK MENUMBUHKAN KEMAMPUAN BERPIKIR DAN KARAKTER ILMIAH SISWA - Wahyu Kurniawati dan Setyo Eko Atmojo (Elementary School: Jurnal Pendidikan dan Pembelajaran ke-SD-an, 2015)
This study aims to develop and test the effectiveness of inquiry-based worksheets onintegrated science teaching in Indonesian lessons in grade 1, 2013. Primary School curriculum to beimproved in the ability to focus on improving the ability of thinking and scientific character ofstudents. The method used in this study is a research & development (R & D) (research anddevelopment). Features developed are integrated inquiry-based worksheets in Indonesian Language.This study was conducted in primary schools in the district, Bantul, Yogyakarta. The instrumentsused in data collection is validation worksheets, test questions thinking skills and student inquiryactivity observation sheet. The results showed that the Inquiry-Based Worksheet in classroom testedon students at four elementary schools earned an average percentage of the control aspects ofelementary students' thinking skills Kadipiro 2 at 78.09%, SD Flower Putihan amounted to 74.00%,SD Bibis by 75.00% and 80.70% of elementary Pity. Worksheet results effectively to foster thedevelopment of a scientific character where the average percentage of students scientific character ineach basic skolah> 70%. Based on these results it can be concluded that the use of SpreadsheetBased beripikir ability to foster inquiry and the scientific character of students in elementary school.